Investigation and determination of the geothermal parameters of the ground in Cyprus for the exploitation of geothermal energy and the impact of the results in the design of the geothermal systems - Partasides, George; Lizides, Andreas; Kassinis, S.; Florides, Georgios A.; Pouloupatis, Panayiotis; Kalogirou, Soteris A.; Messaritis, Vassilios; Panayides, Ioannis; Zomeni, Zomenia; Sophocleous, Eleni; Koutsoumpas, Kostas (My University, 2011)
The Energy Service of the Ministry of Commerce, Industry and Tourism has the overall responsibility for Energy matters in Cyprus and specifically for preparing and implementing programmes for energy conservation, the promotion of renewable energy sources (RES) and the development of technologies for the utilization of RES. The Government of Cyprus being aware of the benefits of geothermal energy and in order to increase the share of energy from renewable sources consumed in heating and cooling in 2020, promotes the geothermal energy systems through a Scheme that provides financial incentives for the utilization of RES for heating and cooling. However, the lack of valid data for the ground thermal properties in Cyprus was one of the main obstacles for the design of efficient geothermal systems, the implementation of the Schemes in the field of geothermal energy and the calculation of the share of energy from renewable sources for heating and cooling according to the methodology defined by the E.U in the directive 2009/28/EC. In an effort to identify suitable energy efficient systems for heating and cooling of buildings and the correct calculations of their contribution to the national targets, the Energy Service participated in a project founded by the Research Promotion Foundation of Cyprus to investigate and determine the geothermal parameters of the ground of Cyprus at six representative sites in Cyprus, for use in the design of ground heat exchanger applications and ground thermal storage. The paper presents the importance of the Isothermal map that helps consultants to design efficiently geothermal energy systems, calculate effectively heat losses of buildings to the ground and design the thermal energy storage equipment. The importance’s of the results are analyzed by national authorities’ experts’ point of view for evaluating geothermal applications bridging in this way the gap between technical output and commercial reality.
Keywords: Geothermal; Ground temperatures; Cyprus Geothermal Map